Analysis of antioxidative and antiviral biomarkers β-amyrin, β-sitosterol, lupeol, ursolic acid in Guiera senegalensis leaves extract by validated HPTLC methods - Mohammad K. Parvez; Perwez Alam; Ahmed H. Arbab; Mohammed S. Al-Dosari; Tawfeq A. Alhowiriny; Saleh I. Alqasoumi (Elsevier, 2018)
Guiera senegalensis J.F. Gmel is a broad-spectrum African folk- medicinal plant, having activities against fowlpox and herpes viruses. Very recently, we have shown the anti-hepatitis B vius (HBV) potential of G. senegalensis leaves extract (GSLE). Here, we report the antioxidative and hepatoprotective efficacy of GSLE, including HPTLC quantification of four biomarkers of known antioxidative and antiviral activities. In cultured liver cells (HuH7) GSLE attenuated DCFH-induced oxidative stress and cytotoxicity. This was supported by in vitro DPPH radical-scavenging and β-carotene-linoleic acid bleaching assays that showed strong antioxidant activity of GSLE. Further, two simple and sensitive HPTLC methods (I and II) were developed and validated to quantify β-amyrin, β- sitosterol, lupeol, ursolic acid in GSLE. While HPTLC-I (hexane: ethylacetate; 75:25; v/v) enabled quantification of β-amyrin (Rf = 0.39; 20.64 μg/mg) and β-sitosterol (Rf = 0.25; 18.56 μg/mg), HPTLC-II (chloroform: methanol; 97:3; v/v) allowed estimation of lupeol (Rf = 0.47; 6.72 μg/mg) and ursolic acid (Rf = 0.23; 5.81 μg/mg) in GSLE. Taken together, the identified biomarkers strongly supported the antioxidant and anti-HBV potential of GSLE, suggesting its activity via abating the oxidative stress. To our knowledge, this is the first report on HPTLC analysis of these biomarkers in G. senegalensis that could be adopted for standardization and quality-control of herbal-formulations. Keywords: Guiera senegalensis, HPTLC, β-Amyrin, β-Sitosterol, Lupeol, Ursolic acid, Antioxidant, Antiviral, Anti-HBV